The relative age effect in elite sport: The French case - Delorme, N.; Boiche, J.; Raspaud, M. (Research Quarterly for Exercise and Sport, 2009)
The relative age effect (RAE) is considered a common phenomenon in elite sport. However, it has not been examined systematically in previous research, and the mechanisms likely to generate or to limit such an effect are little understood. This paper investigates the prevalence of the RAE in French professional championship-level players, taking into account the potential influence of gender. Among all investigated sports, no statistically significant RAE was found, except for male ice hockey. For male handball and rugby union a trend was detected, but the RAE did not appear statistically significant. In line with previous studies, no significant RAEs were found in female elite sports. The results are discussed with regard to the potential mechanisms underlying RAE.